2016
DOI: 10.5139/ijass.2016.17.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Double-array Bolted Joints in Cylindrical Composite Structures

Abstract: A design optimization is performed for the double-bolted joint in cylindrical composite structures by using a simplified analytical method. This method uses failure criteria for the major failure modes of the bolted composite joint. For the doublebolted joint with a zigzag arrangement, it is necessary to consider an interaction effect between the bolt arrays. This paper proposes another failure mode which is determined by angle and distance between two bolts in different arrays and define a failure criterion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…1 *w 1 = −5.34 × 10 −3 t 3 + 2.40 × 10 −1 t 2 – 2.67t + 1. w 2 = −2.74 × 10 −5 t 3 + 2.24 x 10 −3 t 2 – 0.05t + 1. w 3 = 3.21 × 10 −5 t 3 – 1.62 x 10 −3 t 2 + 2.74t + 1. w 4 = 1.…”
Section: Cure Cycle Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 *w 1 = −5.34 × 10 −3 t 3 + 2.40 × 10 −1 t 2 – 2.67t + 1. w 2 = −2.74 × 10 −5 t 3 + 2.24 x 10 −3 t 2 – 0.05t + 1. w 3 = 3.21 × 10 −5 t 3 – 1.62 x 10 −3 t 2 + 2.74t + 1. w 4 = 1.…”
Section: Cure Cycle Modificationmentioning
confidence: 99%
“…The demand for CFRPs has been constantly growing across aerospace, automotive, marine, and wind energy industries as the composite materials offer advantageous mechanical properties such as light weight, high specific strength/stiffness, fatigue life and improved corrosion resistance compared to conventional materials. [1][2][3][4] Traditionally, primary composite structures are manufactured using autoclaves (pressurized ovens), where prepregs-fiber bed reinforcements pre-impregnated with catalyzed yet uncured resin-are consolidated under high pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the bearing capacity was positively correlated with the bolt spacing in the transverse arrangement; while in the longitudinal arrangement, the bearing capacity was positively correlated with the edge distance, and weakly related to the end distance and the bolt spacing. Kim et al [7][8][9][10] Harnessed finite element methods in conjunction with numerical optimization to analyze the performance of diverse bolted connection scenarios. Their studies aimed to determine the optimal arrangement schemes and tightening sequences, with the overarching goal of maximizing the performance of bolted connections.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [11] carried out layout optimization experiments on bolt sets based on the firefly algorithm, and carried out simulation analysis on double-row bolts and three-row bolts, and the optimized bolt layout reduced the perimeter stress of the holes and improved the safety of the structure. However, the optimization of multi-bolt joint structures in the existing literature is limited to symmetric bolt structures [12][13][14][15][16], while there are few studies on asymmetric bolt structures, especially the optimization of a multi-bolt layout in a triangular position. In addition, researchers rarely apply the gray wolf optimization algorithm to the layout optimization of the connection structure of large complex equipment.…”
Section: Introductionmentioning
confidence: 99%